Teknologi Pintar dalam Mewujudkan Kota Berkelanjutan - Reyhand Ardhitha; Tata sutabri (Fakultas Teknik Universitas Cenderawasih, 2024)
This study aims to analyze the role of smart technology in achieving sustainable cities through the implementation of the smart city concept. Using a qualitative approach based on library research, the study explores the relationship between smart technology and urban sustainability, encompassing three main pillars: governance, energy efficiency and environmental management, and social inclusivity. The findings reveal that smart technology enhances transparency and efficiency in governance through e-governance and digital applications, fosters multi-stakeholder collaboration via collaborative governance, and improves government responsiveness to public needs. In the environmental aspect, the implementation of smart technologies such as smart grids and smart sensors significantly contributes to more efficient energy management and carbon emission reductions. Moreover, technology-based waste management demonstrates great potential in supporting urban environmental sustainability. On the social dimension, smart technology must ensure inclusivity by addressing vulnerable groups and bridging the digital divide, where digital literacy and community empowerment play a crucial role in creating sustainable social impacts. However, implementation challenges such as infrastructure gaps, limited budgets, and human resource readiness remain barriers that need to be addressed. This study highlights the importance of integrative and collaborative approaches in smart city implementation, alongside strong strategic policy support to maximize the potential of smart technologies in achieving sustainable development. With the right approach, smart cities can serve as a strategic solution to urbanization complexities and improve the quality of life for future generations.